Stylistic devices used in english texts describing people in ernest hemingway’s novels - Trần Kim Hiếu Hạnh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Ernest Hemingway is a famous writer with a lot of novels and short stories in which his individually unique writing style has influenced both American and global literature up to now. Among his 7 novels, despite the first editions published a long time ago and the different themes- people in a peaceful life in The Sun Also Rises (1926) and people in war in For Whom The Bell Tolls (1940), two novels have been continuously in print ever since. Their attraction may be brought from the love, the friendship, the nature, especially the characters in texts describing people using effectively and skillfully stylistic devices which contribute to the success of two novels. Hence, this thesis attempts to identify and analyze stylistic devices used in English texts describing people in Ernest Hemingway’s novels, particularly his two novels namely The Sun Also Rises and For Whom The Bell Tolls. The analysis, discussions and comments have been made to unveil the stylistic devices in terms of two kinds: lexical and syntacti